Comparative study of antibacterial activity between Cynodon dactylon crude and solid phase extraction extracts against selected bacterial pathogens - Syahriel Abdullah; Januarius Gobilik; Khim-Phin Chong (Bangladesh Pharmacological Society, 2014)
No abstract is available